Flowering of Prunus cerasoides D.Don in its Native Land (The Himalayas) and Some Other Countries in Asia - Umed Kumar Pun; Sudhir Shrestha; Nirajan Bhandari (Nepal Journal of Science and Technology, 2023)
Prunus cerasoides D. Don is the botanical name of the Himalayan cherry and is distributed in the Himalayas and other regions of Asia. Time to defoliation, time to flowering, and flower colour were reviewed in the research database such as Google scholar, ResearchGate and Google. Survey was also carried out in Kathmandu valley, Pokhara, Chitwan of Nepal and Chiang Rai of Thailand to understand the stated parameters. Three colours of flowers were observed in the Himalayan cherry: light pink, white and pink. In the similar locations, light pink type cherry tree flower earlier followed by white whereas flowering was late in pink type flowers. Altitude of the location influenced the time to flower induction and the trend was observed in all the types. This probably could be triggered by lower minimum temperature and was found important to influence flowering time in contrast to the geographical location in the Himalayan region. In South Asian countries, Himalayan cherry flowers from mid part of October to January. However, flowering of Himalayan cherry was found to be in November-December (Japan), December-January (Vietnam), December-February (Thailand) whereas flowering was twice (March-April and August-September) in Indonesia.
Keywords: Phytochemicals and Antioxidant Activities; Phytochemistry and Biological Activities; Plant Physiology and Cultivation Studies